The Need to Protect the Rights and Interests of Workers at Private Health Facilities in Vietnam Without Trade Union - Nguyen Duc Huu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Objectives: To describe the satisfaction of policy policies and the need to participate in trade union organizations and to protect the legitimate rights and interests of workers in private health facilities that have not yet established a trade union organization. Method: Research describing crossings, collecting dosing information via self-filling questionnaires with 299 workers and discussing groups of workers in some health facilities in Hanoi, Ho Chi Minh City and Da Nang. Result: The average satisfaction with the implementation of policies at the unit is >7 points. The need to be represented to protect 15 rights and benefits of cooperation is 7.2-8.2 points. 3/4 workers wishing to join trade unions. Conclusion: In general, employees are quite satisfied with the implementation of some policies at the unit. The need to be represented to protect the legitimate rights and interests of workers in small and medium-sized private medical facilities (general/specialty clinics) as well as the need to join trade unions is common